2016
DOI: 10.1042/bst20150264
|View full text |Cite
|
Sign up to set email alerts
|

Structural comparison of yeast and human intra-mitochondrial lipid transport systems

Abstract: Mitochondria depend on a tightly regulated supply of phospholipids. The protein of relevant evolutionary and lymphoid interest (PRELI)/Ups1 family together with its mitochondrial chaperones [TP53-regulated inhibitor of apoptosis 1 (TRIAP1)/Mdm35] represents a unique heterodimeric lipid-transfer system that is evolutionary conserved from yeast to man. Recent X-ray crystal structures of the human and yeast systems are compared and discuss here and shed new insight into the mechanism of the PRELI/Ups1 system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…We discovered that residues W65 and F69 of the α2-loop would be inserted into the membrane alternately during PA transfer. Although Miliara et al suggested that the α3-helix and the Ω-loop (here, α2-loop) undergo subtle conformational changes, potentially contributing to phospholipid binding and release 26 and speculated that conformational differences in the Ω-loop (here, α2-loop) and α3helix between PRELID1 and PRELID3b are potentially important for lipid specificity 23 , no experimental data have supported this finding. Our disulfide-bridge experiments not only verified these conformational changes but also suggest a synergistic conformational change between the α2-loop and N-α3-helix.…”
Section: Discussionmentioning
confidence: 99%
“…We discovered that residues W65 and F69 of the α2-loop would be inserted into the membrane alternately during PA transfer. Although Miliara et al suggested that the α3-helix and the Ω-loop (here, α2-loop) undergo subtle conformational changes, potentially contributing to phospholipid binding and release 26 and speculated that conformational differences in the Ω-loop (here, α2-loop) and α3helix between PRELID1 and PRELID3b are potentially important for lipid specificity 23 , no experimental data have supported this finding. Our disulfide-bridge experiments not only verified these conformational changes but also suggest a synergistic conformational change between the α2-loop and N-α3-helix.…”
Section: Discussionmentioning
confidence: 99%
“…TRIAP1 is a homolog of MDM35, the sequence and structure of the two are similar, but the N‐terminus of MDM35 also has a short α‐helix, and the C‐terminus is more flexible than TRIAP1 (Figure 3). 367 Similar to MDM35, 368 TRIAP1 can form a heterodimer with protein of relevant evolutionary and lymphoid interest (PRELI) protein and play the role of transporting phospholipids in the mitochondrial intermembrane space 369 . TRIAP1 can inhibit mitochondrial cleavage and the activation of downstream apoptotic protease activating factor‐1 (APAF1)/apoptosome, and play an antiapoptotic effect 370 .…”
Section: Oncogene Triap1: a Novel Target Downstream Of P53mentioning
confidence: 99%
“…While structural analyses and in vitro assays have clearly shown that TRIAP1 interacts with the evolutionary-conserved members of the PRELI family (PRELID1, PRELID3A, and PRELID3B) and is fully capable of carrying out lipid transfer activities for PA and PS, understanding the regulation and the physiological relevance of its mitochondrial action in human cells is still in its infancy (18,(26)(27)(28). The perturbation of TRIAP1/PRELID1-mediated lipid transfer alters the response to apoptotic signals, as it has been reported that knockdown of either TRIAP1 or PRELID1 in HeLa cells partially reduces CL levels, favors the release of cytochrome c, and increases the vulnerability of the cells to apoptosis (26).…”
Section: Introductionmentioning
confidence: 99%